Effects of Cr addition on Charpy impact energy in austenitic 0.45C-24Mn-(0, 3, 6)Cr steels. (1st August 2020) - Lee, Seok Gyu; Kim, Bohee; Jo, Min Cheol; Kim, Kyeong-Min; Lee, Junghoon; Bae, Jinho; Lee, Byeong-Joo; Sohn, Seok Su; Lee, Sunghak
Abstract: Effects of Cr addition (0, 3, and 6 wt%) on Charpy impact properties of Fe-C-Mn-Cr-based steels were studied by conducting dynamic compression tests at room and cryogenic temperatures. At room temperature, deformation mechanisms of Charpy impacted specimens were observed as twinning induced plasticity (TWIP) without any transformation induced plasticity (TRIP) in all the steels. At cryogenic temperature, many twins were populated in the Cr-added steels, but, interestingly, fine ε-martensite was found in the 0Cr steel, satisfying the Shoji-Nishiyama (SN) orientation relationship, { 111 }γ //{ 0002 }ε and < 101 >γ //< 11 2 ¯ 0 >ε . Even though the cryogenic-temperature staking fault energies (SFEs) of the three steel were situated in the TWIP regime, the martensitic transformation was induced by Mn- and Cr-segregated bands. In the 0Cr steel, SFEs of low-(Mn, Cr) bands lay between the TWIP and TRIP regimes which were sensitively affected by a small change of SFE. The dynamic compressive test results well showed the relation between segregation bands and the SFEs. Effects of Cr were known as not only increasing the SFE but also promoting the carbide precipitation. In order to identify the possibility of carbide formation, a precipitation kinetics simulation was conducted, and the predicted fractions of precipitated M 23 C6 were negligible, 0.4–1.1 × 10 −5, even at the low cooling rate of 10 °C/s.